1991
DOI: 10.1038/eye.1991.105
|View full text |Cite
|
Sign up to set email alerts
|

Low Vision Aids—Is our service cost effective?

Abstract: SummaryA questionnaire and telephone survey was carried out on a Scottish population of patients with impaired vision, in order to ascertain the proportion of patients who gain benefit from Low Vision. Aids (LVA) and to determine the number of LVAs which are retained but unused. One third of the patients who answered the question naire never use their LVAs, and one half were not satisfied with the service provided.A cost analysis indicated that approximately (£) 8,000 worth of LVAs are neither used nor returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 7 publications
3
47
1
1
Order By: Relevance
“…McIlwaine et al reported that patients aged <65 years are more likely to use LVAs compared to those aged >65 years, though the difference was not significant. 4 The present findings also indicate that advanced age is a poor prognostic factor for use of LVAs.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…McIlwaine et al reported that patients aged <65 years are more likely to use LVAs compared to those aged >65 years, though the difference was not significant. 4 The present findings also indicate that advanced age is a poor prognostic factor for use of LVAs.…”
Section: Discussionsupporting
confidence: 53%
“…Considerable manual dexterity and motivation are required by patients in order to gain the maximum benefit from LVAs. 4 Low vision rehabilitation is associated with an increase in functional status and improved vision. These positive changes are associated with personal and social benefits, including increased autonomy and enhanced quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies tended to judge the outcomes of a service by either evaluating the frequency of use of low vision aids by patients at follow-up of a variable period 103,131,150 or by assessing clinical measures of visual function, such as visual acuity or reading speed. 69,93,100,107 Although clinical outcomes are important, they do not necessarily reflect the abilities that the patients will show in their home environment; for example, a large discrepancy has been demonstrated between individuals with a good near VA in the clinic (75%), and those able to resolve small print at home (39%).…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
“…[1][2][3][4][5][6] Tüm bunlar hastanın verilen cihazı kullanma başarısını etkilemektedir. [2][3][4][5][7][8][9][10][11][12][13] Yapılan bu çalışmalarda, başvuru esnasındaki görme keskinliği ve hastaların eğitim seviyesi arttıkça uygulanan yardım ve rehabilitasyonun daha başarılı olduğu, merkezi görme alan kaybı ile giden maBölgemizdeki Az Görenlere Yardım Uygulanan Hastaların Etiyolojik Olarak Değerlendirilmesi Ö ÖZ ZE ET T A Am ma aç ç: : Özel Niv Göz Merkezi'ne az görme nedeni ile refere edilen hastaların etiyolojilerini incelemek ve literatür ile karşılaştırmaktır. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Aralık 2010-Mayıs 2015 tarihleri arasında Özel Nivgöz Merkezi'ne az görme nedeni ile refere edilen 464 hastanın 869 gözü retrospektif olarak değerlendirildi.…”
unclassified